Wild and cultivated plant collections from marketplaces of Odisha, India and their role in livelihood support - Panda, Taranisen; Dikshit, Nilamani; Mishra, Nirlipta; Rahimuddin, Shaik; Pradhan, Bikram; Mohanty, Raj Ballav (Ethnobotany Research and Applications, 2023)
Background: Marketplaces serve as valuable sources of information regarding the interactions and relationships between people and plants. In India, the significance of marketplaces remains largely unexplored, despite the country’s remarkable biocultural diversity. To address this research gap, we conducted a study focusing on the diversity of edible wild and cultivated fruits and vegetables available in both rural and urban markets within the Bhadrak district of Odisha, India. Methods: We conducted a comprehensive survey of rural and urban marketplaces in the Bhadrak district of Odisha, India, covering three seasons. Data were collected from 91 informants through semi-structured interviews, key informant discussions, and direct observations. During field visits, voucher specimens were collected and photographs of marketplaces as well as the fruits and vegetables being traded were taken. Results: A total of 93 species, including one species of Pteridophyte, belonging to 37 families and 74 genera, were documented from the markets in the district. Among these species, 53% were native and 47% were non-native. The families Cucurbitaceae and Fabaceae were particularly well-represented. Out of the recorded species, 22 (23.7%) were wild species. Habit analysis revealed that herbs constituted the highest proportion 41.9%, followed by trees 35.5%, Climbers 18.3%, and shrubs 4.3%. According to the majority of informants, wild fruits and vegetables were valued for both their food and medicinal properties. Commonly reported species used for both dietary and medicinal purposes included Glinus oppositifolius (L.) A. DC., Ipomoea aquatica Forrsk., Marsilea minuta L., Moringa oleifera Lam., Syzygium cumini (L.) Skeels, and Tamarindus indica L. When it came to vegetables, leaves, and stems were commonly consumed, while fruits were typically eaten raw. Conclusion: The markets in the Bhadrak district offer a variety of plants, including a wide range of fruits and vegetables. Through analysis of the collected data, it has been revealed that wild fruits and vegetables play a crucial role in generating income and have the potential to become a significant supplementary livelihood option for local farming communities. It is worth noting the dual role of many plant species, serving as dietary components while also contributing to preventive healthcare practices. Market surveys serve as valuable tools for assessing food environments, and the documented food heritage holds great importance in promoting bio-conservation, environmental sustainability, and food security. Keywords: Fruits, Vegetables, Crop biodiversity, Local economy, Wild and cultivated Plants, Medicinal use